Implant Malposition in Prepectoral Breast Reconstruction: Experience with Natrelle® Cohesive Implants over 6.5 Years. Issue 8 (August 2022) - Kuruoglu, Doga; Harless, Christin A.; Tran, Nho V.; Yan, Maria; Martinez-Jorge, Jorys; Nguyen, Minh-Doan T.
Summary: Implant malposition has been reported to be a common reason for revision surgery after implant-based breast reconstruction (IBR). With the recent increase in the use of smooth implants due to concerns for breast implant-associated anaplastic large-cell lymphoma with textured implants, we compared and reported the rates of malposition in prepectoral IBR and identified risk factors. A retrospective review of patients who underwent prepectoral IBR with Natrelle® (Allergan, Inc., Irvine, CA) implants at our institution between January 2014 and May 2020 was performed. Clinical characteristics, implant types, and the rate of malposition, defined as implant flipping or rotation, were recorded. Univariate and multivariable time-to-event analyses using the Cox proportional-hazards model were performed to identify predictors of malposition. Three hundred seventy-five patients (660 breasts) were included. Four hundred forty-one (66.8%) breasts had smooth round implants whereas 219 (33.2%) had textured anatomical devices. Malposition requiring either a manual correction or surgical intervention occurred in 26 (5.9%) smooth round implants versus 3 (1.4%) textured anatomical. Multivariable analysis showed that having a smooth round implant (aHR: 7.19, 95% CI: [2.04 - 25.4]) and an increase in implant volume (aHR: 1.003, 95% CI: [1.001 – 1.006]) were associated with having a malposition requiring intervention. Among smooth round implants; INSPIRA® Cohesive implants were more likely to result in a malposition requiring intervention (p<0.0001) compared to other smooth round implants. Overall, malposition requiring intervention occurred in 5.9% of smooth round implants and 1.4% of textured anatomical implants. Statistical analysis demonstrates that smooth round implants and an increase in implant volume both are associated with a malposition requiring intervention.